Common Antigenic Sites in Human, Bovine and Porcine Fibrinogens - Cierniewski, Czeslaw S (Thrombosis and Haemostasis, 1981)
Specific antisera to the Aα, Bβ and γ chains of porcine fibrinogen were used to characterize an antigenic homology of human, bovine, and porcine fibrinogens. Antigenic determinants shared by these fibrinogens were mostly formed by the Aα chain. However, in the case of bovine and porcine fibrinogens they were also found in the Bβ and γ polypeptide chains. The results reported here show that the Aα chain determinants exposed on the intact fibrinogen molecule are conserved to a considerably larger extent than those of the Bβ and γ chains.
Keywords: Mammalian fibrinogen; Polypeptide chains; Radioimmunoassay